2020
DOI: 10.1074/jbc.ra120.015400
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric activation of proto-oncogene kinase Src by GPCR–beta-arrestin complexes

Abstract: G-protein coupled receptors (GPCRs) initiate signaling cascades via G-proteins and beta-arrestins (βarr). βarr-dependent actions begin with recruitment of βarr to the phosphorylated receptor tail and are followed by the engagement with the receptor core. βarrs are known to act as adaptor proteins binding receptors and various effectors, but it is unclear whether in addition to the scaffolding role βarrs can allosterically activate their downstream targets. Here we demonstrate the direct allosteric activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Many GPCRs are internalized into endosomes via a clathrin-dependent pathway and partly degraded in lysosomes or recycled to the cell membrane for prolonged agonist stimulation [ 36 , 37 , 38 ]. In the present study, the t 1/2 rate indicated slightly faster cell-surface receptor loss in cells expressing the L457R mutant than in cells expressing the wild-type receptor, whereas the rate of loss in the former was slower than for wild-type eLH/CGR, D564G, and D578Y after 30 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many GPCRs are internalized into endosomes via a clathrin-dependent pathway and partly degraded in lysosomes or recycled to the cell membrane for prolonged agonist stimulation [ 36 , 37 , 38 ]. In the present study, the t 1/2 rate indicated slightly faster cell-surface receptor loss in cells expressing the L457R mutant than in cells expressing the wild-type receptor, whereas the rate of loss in the former was slower than for wild-type eLH/CGR, D564G, and D578Y after 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Research is currently underway to clarify our theory on GPCR internalization, degradation, and recycling. Recently, biased allosteric modulators and regulators of other GPCR have been reported [ 36 , 37 , 40 ]. In the present study, the mutants located in the transmembrane domain, and between intracellular loops and the transmembrane domain, demonstrated that eLH/CGRs may be involved in interactions with different types of G-proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that βarr1, activated via either phosphorylated GPCR or the GPCR surrogate V2Rpp (a vasopressin receptor 2 phosphorylated C-terminal peptide with eight phosphates), binds C-Raf and allosterically activates it. Therefore, GPCR-βarr complexes function not just as typical scaffold proteins for the C-J o u r n a l P r e -p r o o f GPCR-βarr1 complexes allosterically activate C-Raf by interacting with its amino-terminus GPCR-βarr complexes have been demonstrated to allosterically activate signaling partners such as the tyrosine kinase Src (22,23). To investigate whether GPCR-βarr complexes allosterically regulate C-Raf activation, we used an enzyme-coupled fluorescence assay to measure the C-Raf activity in real time (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…leading to the adoption of an open active conformation of the kinase [ 76 ]. A further recent study verified that receptor-bound arrestin-2, but not free arrestin-2, is able to activate Src [ 43 ]. Here, the binding of the receptor phospho-tail to arrestin-2 was shown to be sufficient to activate arrestin-2 and therefore Src ( Figure 2 A).…”
Section: Src Activation Through a Gpcr–arrestin Complexmentioning
confidence: 96%